Both subtelomeric regions are required and sufficient for specific DNA fragmentation during macronuclear development in Stylonychia lemnae - Jönsson, Franziska (BioMed Central, 2001)
BACKGROUND: Programmed DNA-reorganization and DNA-elimination events take place frequently during cellular differentiation. An extreme form of such processes, involving DNA reorganization, DNA elimination and DNA fragmentation, is found during macronuclear differentiation in hypotrichous ciliates. Ciliated protozoa can therefore serve as a model system to analyze the molecular basis of these processes during cellular differentiation in eukaryotic cells. RESULTS: Using a biological approach to identify cis-acting sequences involved in DNA fragmentation, we show that in the hypotrichous ciliate Stylonychia lemnae sequences required for specific DNA processing are localized in the 3'- and the 5'-subtelomeric regions of the macronuclear precursor sequence. They can be present at various positions in the two subtelomeric regions, and an interaction between the two regions seems to occur. Sequence comparison revealed a consensus inverted repeat in both subtelomeric regions that is almost identical to the putative Euplotes chromosome breakage sequence (E-Cbs), also identified by sequence comparison. When this sequence was mutagenized, a processed product could no longer be detected, demonstrating that the sequence plays a crucial role in DNA processing. By injecting a construct into the developing macronucleus, which exclusively contains the subtelomeric regions of the Stylonychia αl-tubulin gene, we show that subtelomeric regions are not only required but are also sufficient for DNA processing in Stylonychia. CONCLUSIONS: Our results indicate that an inverted repeat with the core sequence 5'-TGAA present in both subtelomeric regions acts as a Cbs in Stylonychia. The results allow us to propose a mechanistic model for DNA processing in this ciliate.